2008
DOI: 10.1016/j.dr.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent brain

Abstract: Adolescence is a developmental period characterized by suboptimal decisions and actions that give rise to an increased incidence of unintentional injuries and violence, alcohol and drug abuse, unintended pregnancy and sexually transmitted diseases. Traditional neurobiological and cognitive explanations for adolescent behavior have failed to account for the nonlinear changes in behavior observed during adolescence, relative to childhood and adulthood. This review provides a biologically plausible conceptualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

60
1,146
7
35

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,567 publications
(1,248 citation statements)
references
References 83 publications
60
1,146
7
35
Order By: Relevance
“…This paradox appears driven by the fact that social, reward and affective "hot" contexts influence adolescents' cognition and behaviour to a greater extent than is observed in adults (Albert, Chein, & Steinberg, 2013;Casey & Caudle, 2013). On the basis of such observations, it has been proposed that adolescents' risk-taking and susceptibility to peer influence may partly derive from differences in the maturational timecourse of the socio-emotional reward system and the cognitive control system in the brain (Albert et al, 2013;Casey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paradox appears driven by the fact that social, reward and affective "hot" contexts influence adolescents' cognition and behaviour to a greater extent than is observed in adults (Albert, Chein, & Steinberg, 2013;Casey & Caudle, 2013). On the basis of such observations, it has been proposed that adolescents' risk-taking and susceptibility to peer influence may partly derive from differences in the maturational timecourse of the socio-emotional reward system and the cognitive control system in the brain (Albert et al, 2013;Casey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two decades of cognitive neuroscience research suggest that adolescence is associated with increasing use of top-down cognitive control skills, which allows adolescents to focus their attention and regulate their emotions and behaviour in order to achieve their goals (Crone & Dahl, 2012). However, adolescence is also associated with sub-optimal decisions and actions apparent in heightened substance abuse and mortality rates (Casey, Getz, & Galvan, 2008;Dahl, 2004;Steinberg, 2008; although see Willoughby, Good, Adachi, Hamza, & Tavernier, 2013). This paradox appears driven by the fact that social, reward and affective "hot" contexts influence adolescents' cognition and behaviour to a greater extent than is observed in adults (Albert, Chein, & Steinberg, 2013;Casey & Caudle, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En efecto, desde la caracterización de la adolescencia como un periodo de "tormenta y tensión" que presentara Stanley Hall (1904), pasando por la proposición de una "adultez emergente" (Arnett, 2000), se han ido desarrollando miradas más complejas sobre los cambios que experimentan adolescentes y jóvenes. En ese sentido, por ejemplo, cabe mencionar los diferentes modelos de organización del cerebro adolescente y joven que se agrupan bajo la denominación de Modelos de Sistemas Duales (ver, por ejemplo: Casey, Getz, & Galván, 2008;Shulman et al, 2016). Estos modelos consideran que hay un desarrollo asimétrico entre las estructuras encargadas del procesamiento y del control cognitivo, y aquellas encargadas del procesamiento de información socioemocional (Steinberg, 2008).…”
unclassified
“…According to Casey, Getz, and Galvan (2008), imaging studies have demonstrated that developmental maturation occurs in the brain of the adolescence. The authors purported that a more mature limbic system (pleasure seeking) and a less developed prefrontal cortex (controlling behaviors), while not seen as sole contributors to the impulsivity and high risk actions of adolescents may explain some of the activities of adolescents including unprotected sex resulting in unplanned pregnancies.…”
Section: Adolescent Developmental Tasksmentioning
confidence: 99%